Numerical Analysis in MHD of Casson Fluid Flow Over Stretching Sheet - Ahmadi, Muhammad Salman; Md Shab, Noorzehan Fazahiyah (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This paper  about study the numerical analysis in MHD of Casson fluid induced by a stretching sheet. Casson fluid plays important roles for application in industry and technology. The aim of the present study is to investigate the physical behaviour of velocity, thermal fields, skin friction and Nusselt number that affected by the parameters (magnetic fields parameter (M), Casson fluid parameter (b) and Prandtl number (Pr)) on Casson fluid that flow over a stretching sheet. First, the governing partial differential equations are transformed into a system of ordinary differential equations by similarity transformation. The system is solved numerically using a shooting method with RK45 with the help of Maple software. Then, velocity and thermal fields are graphically discussed. Furthermore, the numerical results of skin friction and Nusselt number are also shown in the tabular form. As a result, it is revealed that velocity decreased and thermal increased for the larger magnetic field parameter, (M). Moreover, velocity and thermal fields will be decreased when the Casson fluid parameter(b) and Prandtl number, (Pr) are increasing. Besides that, the skin friction coefficient is increasing when b and M increase. Nusselt number increases when the larger value Pr is used. The opposite situation is noticed for higher (M).